2020
DOI: 10.1088/1742-6596/1529/2/022008
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Focus Attention Instructions on the Movement Kinetics, Muscle Activation and Performance during Resistance Exercise

Abstract: The aim of this study was to compare kinetics, muscle activation and performance during resistance exercises between internal focus attention instructions, external focus attention instructions and control condition. Thirty (n = 30, mean age = 21.40 ± 0.93 years old) healthy men were recruited as participants and were asked to perform resistance exercises in three conditions; i) internal focus, ii) external focus and iii) control (no focus attention instruction). Participants performed 10RM squat and deadlift … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(17 citation statements)
references
References 15 publications
0
17
0
Order By: Relevance
“…Out of this pool of references, 124 results were excluded based on the title or abstract. Therefore, 20 full-text studies were read and four studies [ 8 , 10 , 11 , 12 ] were found to satisfy the inclusion criteria. In the secondary search, there were 285 search results.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Out of this pool of references, 124 results were excluded based on the title or abstract. Therefore, 20 full-text studies were read and four studies [ 8 , 10 , 11 , 12 ] were found to satisfy the inclusion criteria. In the secondary search, there were 285 search results.…”
Section: Resultsmentioning
confidence: 99%
“…We excluded 284 based on title, abstract, or full-text, and one study [ 9 ] was additionally included. Therefore, a total of five studies were included in the review ( Figure 1 ) [ 8 , 9 , 10 , 11 , 12 ]. One study included male and female participants and explored sex-specific effects [ 8 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations